Georges Bigot and Japan, 1882-1899 : satirist, illustrator and artist extraordinaire - Bigot, Georges, 1860-1927 (Renaissance Books, 2018)
"Incorporating over 250 illustrations, this is the first comprehensive study in English of French artist and caricaturist Georges Ferdinand Bigot (1860-1927) who during the last two decades of the nineteenth century recorded the changing face of Japan as its people, politics and preoccupations moved from their traditional cultural base to become a modern, industrialized state."--Back cover.